Ecobrick Making Assistance Towards Sustainable Environmental Health in Lumajang East Java through Asset-Based Community Development - Taufiq, Amal; Aji Al Fazza, Daffa (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
Tempeh Tengah village is one of the Lumajang district villages with a waste problem, especially plastic waste. This service activity aims to overcome this problem by turning plastic waste into eco-bricks because it is relatively easy and can be done by anyone, both children and adults. This community service uses the Asset Based Community Development (ABCD) approach, which views everyone has capacities and needs to be explored and mobilized. The results of this community service show that to execute the expectations above, the subsequent activities are conducted in environmental sanitation (Source Tiyo), enhancing the environment, creating trash bins from bamboo, and management of waste banks. There has been a significant change in the community, especially in changing the mindset of viewing waste as an asset by processing it into eco-bricks. To ensure the continuity of the program in the community, the KKN team formed a core group by training students at Islamic boarding schools about the importance of maintaining environmental health. Hopefully, this program will be expanded on a larger scale to maximize its benefits and positively impact environmental sustainability.